An Insight on Multicentric Signaling of Angiotensin II in Cardiovascular system: A Recent Update - Verma, Kanika; Pant, Malvika; Paliwal, Sarvesh; Dwivedi, Jaya; Sharma, Swapnil (Frontiers in Pharmacology, 2021)
The multifaceted nature of the renin-angiotensin system (RAS) makes it versatile due to its involvement in pathogenesis of the cardiovascular disease. Angiotensin II (Ang II), a multifaceted member of RAS family is known to have various potential effects. The knowledge of this peptide has immensely ameliorated after meticulous research for decades. Several studies have evidenced angiotensin I receptor (AT1 R) to mediate the majority Ang II-regulated functions in the system. Functional crosstalk between AT1 R mediated signal transduction cascades and other signaling pathways has been recognized. The review will provide an up-to-date information and recent discoveries involved in Ang II receptor signal transduction and their functional significance in the cardiovascular system for potential translation in therapeutics. Moreover, the review also focuses on the role of stem cell-based therapies in the cardiovascular system.